2018
DOI: 10.1016/j.immuni.2018.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Human IFIT3 Modulates IFIT1 RNA Binding Specificity and Protein Stability

Abstract: SUMMARY Interferon-induced proteins with tetratricopeptide repeats (IFIT) inhibit infection of many viruses by recognizing their RNA, but the mechanisms regulating their remain unclear. We report a crystal structure of cap 0 (m7GpppN)-RNA-bound to human IFIT1 in complex with the C-terminal domain of human IFIT3. Structural, biochemical, and genetic studies suggest that IFIT3 binding to IFIT1 has dual regulatory functions: (a) extending the half-life of IFIT1, which increases its steady-state levels in cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
159
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(166 citation statements)
references
References 40 publications
7
159
0
Order By: Relevance
“…mRNAs that lack Cap 1 2’O methylation are known to be preferentially bound by IFIT1 (13, 19-22, 25, 27, 30, 42), and the translation of viral RNAs lacking Cap 1 2’O methylation is known to be inhibited by IFIT1 (20, 21, 42). Therefore, we hypothesized that the protein expression of host transcripts lacking Cap 1 2’O methylation may be inhibited by IFIT1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…mRNAs that lack Cap 1 2’O methylation are known to be preferentially bound by IFIT1 (13, 19-22, 25, 27, 30, 42), and the translation of viral RNAs lacking Cap 1 2’O methylation is known to be inhibited by IFIT1 (20, 21, 42). Therefore, we hypothesized that the protein expression of host transcripts lacking Cap 1 2’O methylation may be inhibited by IFIT1.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we found that depletion of IFIT1 rescued the protein expression of ISG15, MX1, and IFITM1 resulting in equivalent expression of ISGs following CMTR1 depletion as compared to control in IFN-β-treated Huh7 cells ( Figure 4-B ). We did not examine IFIT3 in this assay, as it is in a complex with IFIT1 alterations in IFIT1 levels likely also IFIT3 expression (20, 21, 43). Therefore, the translational repression of the CMTR1-dependent ISGs is mediated through the actions of IFIT1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interferon-stimulated genes (ISGs) are a large group of genes which have diverse effects on viral infections and mostly act at early stages of virus life-cycle (53). The IFIT proteins are a family of antiviral proteins that form complexes to target viral RNA and inhibit translation (54)(55)(56). Although DENV has been shown to evade interferon responses, induction of ISGs at very early stages before the accumulation of viral proteins that target some of the innate immune components may tip the balance in favor of innate immune responses and block viral RNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…We also show here that the G5-TPR alone does not interact with RNA, irrespectively of whether it consisted of single or double stranded molecules, short hairpins, long stem-loops, or DNA ( Figure 3). This result establishes a main difference with proteins carrying TPR domains involved in RNA-dependent pathways or in direct RNA-binding (Abbas et al, 2013;Grotwinkel et al, 2014;Johnson et al, 2018;Katibah et al, 2013;Yang et al, 2012;Zhou et al, 2018). The high sequence conservation of the TPR-like domain strongly suggests that the dimerization module of Gemin5 plays a fundamental role for the architecture and activity of the protein.…”
Section: Discussionmentioning
confidence: 83%